Factors that influence employee's perception towards sexual harassment - Noor Akhma, Binti Mohd Nawi. (Universiti Malaysia Sarawak (UNIMAS), 2010)
This study aims to identify the factors that influence employee's perception towards sexual harassment at the workplace. The employee's perception was investigated from related aspect such as, level of awareness, work environment, organizational policy and preventive actions. The aim of this research is to identify factors that lead to sexual harassment at the workplace in Malaysia. Its objectives are to identify a significant relationship between level of awareness, work environment, organizational policy and preventive actions and employee's perception towards sexual harassment as well as to identify the differences between gender and employee's perception towards sexual harassment and to identify dominant factor that leads to sexual harassment at the workplace. This research design is quantitative study using survey methodology whereas a questionnaire designed by the past researchers was randomly distributed to 60 employees at the supermarket in Kota Samarahan, Sarawak. Data processing was analyzed using Statistical Package for the Social Science (SPSS 15.0) software to find the frequency, mean and standard deviation. Meanwhile, Independent T-test, Pearson Correlation Analysis, and Multiple Regression were used to analyze the hypotheses. The findings showed that there is a significant relationship between work environment and employee's perception towards sexual harassment. However, the other finding indicates that there is no significant relationship between level of awareness, preventive actions and organizational policy with employee's perception towards sexual harassment. This research fording also found that there is no difference between gender and employee's perception towards sexual harassment at the workplace. Meanwhile, Multiple Regression Analysis was used to identify dominant factor that influence employee's perception towards sexual harassment at the workplace and the result showed that work environment is the dominant factor which 14.2% changes in employee's perception towards sexual harassment was caused by work environment.